2016
DOI: 10.1186/s40510-016-0152-y
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of nanosilver-coated orthodontic brackets: an in vivo study

Abstract: BackgroundNanosilver particles of which antibacterial and antifungal properties have been shown in various in vitro and in vivo studies are used in many medical and dental fields for the prevention of infection. In this study, it is intended to evaluate the biocompatibility of nanosilver-coated brackets.MethodsNanosilver coating process was applied to the standard orthodontic brackets by a physical vapor deposition system. Brackets were coated with nanosilver particles of 1 μ thickness. A total of 12 Wistar Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Recently, nanotechnology has gained attention for dental applications. [12][13][14][15][16][17][18][19] Zinc oxide 20 and silver [20][21][22][23] nanoparticles as well as iron oxide nanozymes (NZM) 12 have been proposed as antibiofilm agents. In particular, uncoated NZM displayed potent antibiofilm actions due to their high peroxidase-like catalytic activity in acidic environments, 12 which can disrupt caries development in the presence of low concentrations of H 2 O 2 .…”
mentioning
confidence: 99%
“…Recently, nanotechnology has gained attention for dental applications. [12][13][14][15][16][17][18][19] Zinc oxide 20 and silver [20][21][22][23] nanoparticles as well as iron oxide nanozymes (NZM) 12 have been proposed as antibiofilm agents. In particular, uncoated NZM displayed potent antibiofilm actions due to their high peroxidase-like catalytic activity in acidic environments, 12 which can disrupt caries development in the presence of low concentrations of H 2 O 2 .…”
mentioning
confidence: 99%
“…Gamze in a study found a significantly lowered mast cell count and suggested that nanosilver-coated orthodontic brackets have better tissue compatibility than standard orthodontic brackets. [ 21 ] In the oral cavity, mitotic activity occurs in the basal layer of the epithelium, which is exfoliated into the oral cavity within 14 days. Hence, any genetic damage caused by continuous uptake of toxic ions released from the metal alloys or due to trauma in the mucosal cells can be reflected in the exfoliated cells as micronuclei, binucleated cell, broken egg, karyolysis, karyorrhexis, and pycknosis.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of silver nanoparticles to the bonding system affected the shear bond strength of the orthodontic brackets to enamel. [9,11]. Sonja Blocher et al, demonstrated the addition of micro silver or AgNPs to an orthodontic primer which affected shear bond strength (SBS) and bracket/adhesive failure.…”
Section: Sheer Bond Strength Of Orthodontic Bracketsmentioning
confidence: 99%